THE USE OF STUDENTS TEAMS ACHIEVEMENT DIVISIONS (STAD) METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION (A STUDY IS CONDUCTED AT SMP N 3 TOMOHON) - Roland Mandagi; Noldy Pelenkahu; Jennie Posumah (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study was to find out whether the use of the application of Students Teams Achievement Division (STAD) method is able to improve students’ reading comprehension. The students at SMP N 3 Tomohon in academic year 2020/2021 were chosen as the subject of this study, specified to the seventh grade that consisted 30 students. This research used pre- experimental design with one group pre-test and post-test. This study consited in five meetings. First the researcher gave a pre-test. Second, treatment and the last posttest. This technique in collecting data used test as instrument in form of multiple choice test consisted with 30 numbers. The result of this study found that STAD was effective in improving students’ reading comprehension posttest was higher than pretest. The mean score pretest was 40.5 and the mean score of posttest was 62.66. It can be stated that STAD is considered effective to increase students’ vocabulary.